2021
DOI: 10.3329/aajfss.v5i2.56958
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination and antibiotic residues in poultry feed and meat in Bangladesh

Abstract: Presence of harmful contaminants and residues in poultry feed and meat have serious public health consequence. This study was carried out to identify and quantify antibiotic residues, heavy metals and toxins in poultry feed and meat in the two selected poultry production belts of Bangladesh. A total of 94 broiler feed samples and 60 broiler meat samples were collected and tested by Thin Layer Chromatography (TLC), High Performance Liquid Chromatography (HPLC) and Enzyme-linked Immunosorbent Assay (ELISA) for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…No sample was affirmative for enrofloxacin. Similar study on poultry feed samples in Bangladesh showed the presence of antibiotic residues in 18.89% samples [33]. The results of present study indicate that in recent years, indiscriminate use of antibiotics in poultry feed has drastically increased which is a matter of concern.…”
Section: Antibiotics Residue In Poultry Feedsupporting
confidence: 79%
“…No sample was affirmative for enrofloxacin. Similar study on poultry feed samples in Bangladesh showed the presence of antibiotic residues in 18.89% samples [33]. The results of present study indicate that in recent years, indiscriminate use of antibiotics in poultry feed has drastically increased which is a matter of concern.…”
Section: Antibiotics Residue In Poultry Feedsupporting
confidence: 79%
“…In this study, among 120 poultry feed samples, 19 (15.83%) were residue positive with 13 (10.83%) oxytetracycline, 3 (2.5%) doxycycline, and 3 (2.5%) ciprofloxacin ( Table-2 ). Another study uncovered that about 18.89% of poultry feed samples were enriched with antibiotic residues in Bangladesh [ 38 ]. Other researchers have also found the presence of antibiotic residues in poultry feed, including enrofloxacin (46.67%), ciprofloxacin (30.00%), and amoxicillin (23.33%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%